Gender differences in response to a school-based mindfulness training intervention for early adolescents. (June 2018) - Kang, Yoona; Rahrig, Hadley; Eichel, Kristina; Niles, Halsey F.; Rocha, Tomas; Lepp, Nathaniel E.; Gold, Jonathan; Britton, Willoughby B.
Abstract: Mindfulness training has been used to improve emotional wellbeing in early adolescents. However, little is known about treatment outcome moderators, or individual differences that may differentially impact responses to treatment. The current study focused on gender as a potential moderator for affective outcomes in response to school-based mindfulness training. Sixth grade students ( N = 100) were randomly assigned to either the six weeks of mindfulness meditation or the active control group as part of a history class curriculum. Participants in the mindfulness meditation group completed short mindfulness meditation sessions four to five times per week, in addition to didactic instruction (Asian history). The control group received matched experiential activity in addition to didactic instruction (African history) from the same teacher with no meditation component. Self-reported measures of emotional wellbeing/affect, mindfulness, and self-compassion were obtained at pre and post intervention. Meditators reported greater improvement in emotional wellbeing compared to those in the control group. Importantly, gender differences were detected, such that female meditators reported greater increases in positive affect compared to females in the control group, whereas male meditators and control males displayed equivalent gains. Uniquely among females but not males, increases in self-reported self-compassion were associated with improvements in affect. These findings support the efficacy of school-based mindfulness interventions, and interventions tailored to accommodate distinct developmental needs of female and male adolescents.